Synthesis of Spinal Lithium-Titanium Oxide Lithium Ion-Sieve by Solid State Reaction Crystallization Method - Jiang, Jinhe (Asian Journal of Chemistry, 2012)
The Li3Ti1.25O4 was synthesized by a solid state reaction crystallization method using lithium carbonate and titanium dioxide as raw materials. The optimum conditions were obtained by thermal experiment, calcination temperature was 775 ºC, calcination time was 4.5 h. The characterization results showed that the exchange capacity of Li+ was 9.3 mmol g-1 for Li+ in the solution.